2006
DOI: 10.1073/pnas.0606544103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of brain neurons that express enzymes mediating neurosteroid biosynthesis

Abstract: Allopregnanolone (ALLO) and tetrahydrodeoxycorticosterone (THDOC) are potent positive allosteric modulators of GABA action at GABAA receptors. ALLO and THDOC are synthesized in the brain from progesterone or deoxycorticosterone, respectively, by the sequential action of two enzymes: 5␣-reductase (5␣-R) type I and 3␣-hydroxysteroid dehydrogenase (3␣-HSD). This study evaluates 5␣-R type I and 3␣-HSD mRNA expression level in mouse brain by using in situ hybridization combined with glutamic acid decarboxylase 67͞6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
337
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(352 citation statements)
references
References 55 publications
11
337
0
4
Order By: Relevance
“…It has previously been shown that mRNA levels of the enzymes are correlated with protein amounts and activities in other studies [46][47][48][49][50] so we did not repeat these studies.…”
Section: Discussionmentioning
confidence: 40%
“…It has previously been shown that mRNA levels of the enzymes are correlated with protein amounts and activities in other studies [46][47][48][49][50] so we did not repeat these studies.…”
Section: Discussionmentioning
confidence: 40%
“…This pattern of 3a,5a-THP expression corresponds with expression of the biosynthetic enzymes 5a-R and 3a-HSD needed for 3a,5a-THP synthesis and metabolism (Agis-Balboa et al, 2006). Therefore, it has been suggested that a major role of 3a,5a-THP may be to modulate neurocircuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Given the preference of steroids to affiliate with intracellular and plasma membranes, another implication of these considerations is that autocrine/paracrine actions of endogenous steroids may be particularly important. Recently, it has been suggested that neurosteroid synthetic enzymes are localized within principal, projection neurons in many CNS regions, but not in interneurons (Agis-Balboa et al, 2006). If autocrine actions are particularly important because of lipophilic retention, then we might expect cell-specificity in the actions of endogenous steroids.…”
Section: A Access To Sitesmentioning
confidence: 99%